Preoperative Patient Optimization in Total Joint Arthroplasty—The Paradigm Shift from Preoperative Clearance: A Narrative Review. Issue 3 (August 2022) - MacMahon, Aoife; Rao, Sandesh S.; Chaudhry, Yash P.; Hasan, Syed A.; Epstein, Jeremy A.; Hegde, Vishal; Valaik, Daniel J.; Oni, Julius K.; Sterling, Robert S.; Khanuja, Harpal S.
Background: Total joint arthroplasty (TJA) is one of the most common procedures performed in the United States. Outcomes of this elective procedure may be improved via preoperative optimization of modifiable risk factors. Purposes: We sought to summarize the literature on the clinical implications of preoperative risk factors in TJA and to develop recommendations regarding preoperative optimization of these risk factors. Methods: We searched PubMed in August 2019 with an update in September 2020 for English-language, peer-reviewed publications assessing the influence on outcomes in total hip and knee replacement of 7 preoperative risk factors—obesity, malnutrition, hypoalbuminemia, diabetes, anemia, smoking, and opioid use—and recommendations to mitigate them. Results: Sixty-nine studies were identified, including 3 randomized controlled trials, 8 prospective cohort studies, 42 retrospective studies, 6 systematic reviews, 3 narrative reviews, and 7 consensus guidelines. These studies described worse outcomes associated with these 7 risk factors, including increased rates of in-hospital complications, transfusions, periprosthetic joint infections, revisions, and deaths. Recommendations for strategies to screen and address these risk factors are provided. Conclusions: Risk factors can be optimized, with evidence suggesting the following thresholds prior to surgery: a body mass index <40 kg/m 2, serum albumin ≥3.5 g/dL, hemoglobin A1C ≤7.5%, hemoglobin >12.0 g/dL in women and >13.0 g/dL in men, and smoking cessation and ≥50% decrease in opioid use by 4 weeks prior to surgery. Surgery should be delayed until these risk factors are adequately optimized.